2006
DOI: 10.4049/jimmunol.177.2.1264
|View full text |Cite
|
Sign up to set email alerts
|

Signaling via Platelet-Activating Factor Receptors Accounts for the Impairment of Neutrophil Migration in Polymicrobial Sepsis

Abstract: Sepsis is a systemic inflammatory response that results from the inability of the immune system to limit bacterial spread during an ongoing infection. Recently, we have documented an impaired neutrophil migration toward the infectious focus in severe sepsis. This impairment seems to be mediated by circulating cytokines, chemokines, and NO. Platelet-activating factor (PAF) plays an important role in the orchestration of different inflammatory reactions, including the release of cytokines, chemokines, and free r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 59 publications
2
37
0
1
Order By: Relevance
“…Moreno et al (45) showed that blockade of PAFR signaling was associated with an enhancement of neutrophil migration to the infectious site in a model of polymicrobial sepsis, which is in line with our findings. Because in their study PAFR blockade was associated with decreased bacterial outgrowth, the increased neutrophil migration to the peritoneal cavity during PAFR blockade was unlikely to be the consequence of a higher bacterial load.…”
Section: Discussionsupporting
confidence: 82%
“…Moreno et al (45) showed that blockade of PAFR signaling was associated with an enhancement of neutrophil migration to the infectious site in a model of polymicrobial sepsis, which is in line with our findings. Because in their study PAFR blockade was associated with decreased bacterial outgrowth, the increased neutrophil migration to the peritoneal cavity during PAFR blockade was unlikely to be the consequence of a higher bacterial load.…”
Section: Discussionsupporting
confidence: 82%
“…In contrast to clinical shock trials where the drug is given in patients already with disease, most experimental studies only evaluated the effects of preventive administration of PAFR antagonists. PAFR antagonists clearly lose their efficacy when administered after the inciting stimulus in models of septic or anaphylactic shock (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…4248 (5 mg/kg/dose, s.c., B.I.D) (23). In some experiments, mice were pretreated with non-immune serum or serum (1 single dose of 100 L of 1:10 dilution of stock serum in PBS, i.p., 60 min before inoculation) obtained from Rhesus monkeys previously infected with a known DEN-2 strain (31) (kindly donated by Dr Ricardo Galler, Fiocruz, Brazil).…”
mentioning
confidence: 99%
“…In vivo sepsis analysis was performed according to the method proposed by Moreno et al 33 involving intraperitoneal sepsis induction in mice using an injection containing a bacteria pool. For in vivo experiments, C57BL/6 mice were obtained from the Universidade Católica Dom Bosco, housed in temperature-controlled cages (22°C-24°C), and received food and water ad libitum.…”
Section: In Vivo Antibacterial Activitiesmentioning
confidence: 99%